Mobility management - T. N. Sakulyeva (Управление)
The mobility management concept encompasses various services, organisational and advisory measures that allow users to change their travel choices.The article investigates various aspects and factors of mobility management policy. The transport behavior, the possibilities and expediency of joint trips, cycling and walking, the issues of changing transport behavior and making changes in transport infrastructure were studied. The cost-effective options for improving the road use efficiency, the volume and quality of information given to traffic participants as well as the intensity of its provision, which ensure the success of the mobility management policy, were analysed.The comprehensive policy in the field of bicycle and pedestrian traffic is necessary at the city level or even at the national level linked to the policy of urban development for the successful use of bicycle and pedestrian transport. The mobility management policy directed to encourage the wider use of cycling and pedestrian transport should be aimed to removing barriers obstructing their use. It is also necessary to make changes in existing infrastructure in order to increase the traffic capacity during rush hours.